Going Green with UMPs Research & Innovation - Muhammad Aizat, Azed (2022)
KUANTAN, 22 February 2022 – The UMP Strategic Plan 2021-2025 through Strategic Objective-3 has emphasized the importance of exploring high-impact technologies that bring positive changes to the community.